LEGAL PROTECTION OF THE CHILD IN EDUCATION AND THE FORMATION OF LEGAL CULTURE OF CHILDREN IN THE LEARNING PROCESS - Nataliya A Bylinskaya (Universitas Brawijaya, 2019)
The article is devoted to the actual problems of legal protection of children in the field of education, informing the child in the process of learning about his rights and freedoms, duties and responsibilities. Providing children with useful, necessary and relevant information that contributes to the formation of the child's correct understanding of good and evil, respect for other people, the correctness or inadmissibility of certain actions is a necessary and important emphasis of the education system, affecting the birth of the child's sense of justice. In particular, the author considers and analyzes the legal aspect of obtaining this information by the child, the degree of its protection in the process of education, the level of development of Russian legislation in this area. The author critically reviews the absence of the Institute of legal culture in children, which is positioned today as one of the fundamental tasks of the national education system, but in reality is absent.